1984
DOI: 10.1038/ki.1984.94
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic roles of post-heparin lipases in lipid abnormalities in hemodialysis patients

Abstract: The relative roles of hepatic lipase and lipoprotein lipase in the pathogenesis of uremic lipid abnormalities were studied in 92 hemodialysis patients. Fasting serum cholesterol, triglyceride, and HDL-cholesterol concentrations were measured. Plasma lipoprotein electrophoretic patterns were determined in all patients. Hepatic lipase and lipoprotein lipase activities were selectively measured in post-heparin plasma in 59 patients. Hemodialysis patients had higher serum triglyceride and lower HDL-cholesterol con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(48 citation statements)
references
References 28 publications
1
47
0
Order By: Relevance
“…Such abnormalities are seen in ESRD patients who are not on dialysis [4] and also in patients treated either by chronic hemodialysis (CHD) [5] or continuous peritoneal dialysis (CPD) [6, 7]. Low-density lipoprotein cholesterol (LDL-C) levels are not elevated in ESRD patients [6, 8], but changes in LDL size and composition in association with hypertriglyceridemia could potentially result in increased atherogenicity of LDL particles [9].…”
Section: Introductionmentioning
confidence: 99%
“…Such abnormalities are seen in ESRD patients who are not on dialysis [4] and also in patients treated either by chronic hemodialysis (CHD) [5] or continuous peritoneal dialysis (CPD) [6, 7]. Low-density lipoprotein cholesterol (LDL-C) levels are not elevated in ESRD patients [6, 8], but changes in LDL size and composition in association with hypertriglyceridemia could potentially result in increased atherogenicity of LDL particles [9].…”
Section: Introductionmentioning
confidence: 99%
“…14 The abnormal lipid composition of all lipoprotein classes has been reported to be caused mainly by a combination of an impaired reversed cholesterol transport 11 and lipolytic cascade. 15 To date, only 2 apoB kinetic studies have been reported in HD patients: Chan et al injected radio-labeled VLDL into HD patients with or without hyperlipidemia and found decreased fractional catabolic rates (FCR) of VLDL-and IDL-apoB (the latter only in hyperlipidemic patients). 16 Unfortunately, the LDL turnover was not investigated in this study.…”
mentioning
confidence: 99%
“…Several investigators indicate decreased lipo protein lipase activity in renal failure (10,12). Regarding the mechanism behind the decrease in LPL activity in uremia, three theories prevail, all of them supported by clinical or experimental findings: i) reduced enzyme synthesis by the parenchyma cell; ii) circulating inhibitor(s) against the enzyme activity and iii) heparin induced depletion of the functional enzyme pool (in hemodialysis patients).…”
Section: Introductionmentioning
confidence: 78%